2020
DOI: 10.3390/cosmetics7010014
|View full text |Cite
|
Sign up to set email alerts
|

Sunscreen Boosting Effect by Solid Lipid Nanoparticles-Loaded Fucoxanthin Formulation

Abstract: Fucoxanthin is a bioactive compound that is a kind of natural carotenoid. Fucoxanthin is known to protect against UV-B-induced cell damage in hairless mice, even though it is physiochemically unstable to heat and acid due to its polyunsaturated structure, indicating that fucoxanthin possesses a low bioavailability, and this disadvantage limits its application in the cosmetic industry. Solid lipid nanoparticle (SLN) systems are known to be suitable as carriers for sunscreen agents. In this research work, the su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 12 publications
0
11
0
Order By: Relevance
“…For instance, a topical formulation containing fucoxanthin has been developed that could prevent exacerbations related to skin inflammatory pathologies and protect skin against UV radiation [159]. In addition, solid lipid nanoparticle formulation loaded with fucoxanthin demonstrated the UV-blocking potential [160]. Furthermore, Kang et al (2020) reported that fucoxanthin concentrate extracted from P. tricornutum could be utilized as an active ingredient in wrinkle care cosmetics [161].…”
Section: Commercial Products and Potential Applications Of Fucoxanthinmentioning
confidence: 99%
“…For instance, a topical formulation containing fucoxanthin has been developed that could prevent exacerbations related to skin inflammatory pathologies and protect skin against UV radiation [159]. In addition, solid lipid nanoparticle formulation loaded with fucoxanthin demonstrated the UV-blocking potential [160]. Furthermore, Kang et al (2020) reported that fucoxanthin concentrate extracted from P. tricornutum could be utilized as an active ingredient in wrinkle care cosmetics [161].…”
Section: Commercial Products and Potential Applications Of Fucoxanthinmentioning
confidence: 99%
“…They show improved biocompatibility and safety and act as a successful transporter delivery system in cosmeceutical applications [ 12 ]. Since 2005, SLNs have been used in several dermal cosmetic products to achieve good outcomes [ 83 , 84 ]. SLNs are widely used in formulating sunscreens, where they act as active carriers for molecular sunscreen agents.…”
Section: Nano-drug Delivery Systems Used In Cosmeticsmentioning
confidence: 99%
“…A recent experimental study carried out on an SLN formulation integrating fucoxanthin (protects against UVB light) concluded that the presence of the SLN carrier improved the bioavailability of fucoxanthin and can be a promising carrier for sunscreen cosmetics, showing greater stability and good sunscreen-boosting action [ 84 , 87 ]. Another study combined the capability of the flavonoid as a natural antioxidant with NLCs to form an effective system for delivery into the cells.…”
Section: Nano-drug Delivery Systems Used In Cosmeticsmentioning
confidence: 99%
“…These results seem to indicate that the oral or topical administration of fucoxanthin can prevent or even reduce the negative effects induced by UV radiation exposure, such as the appearance of melanomas. In fact, due to its antioxidant capacity, fucoxanthin has been tested in several anti-aging and anti-sun cosmetic formulations [101,102]. In the cosmetics and pharmaceutical industries, this carotenoid is also relevant, due to its skin protective effects against burns and filaggrin (filament aggregating protein) disorder induced by radiation.…”
Section: Developed Products Containing Fucoxanthin and Their Health Bmentioning
confidence: 99%
“…These results seem to indicate that the oral or topical administration of fucoxanthin can prevent or even reduce the negative effects induced by UV radiation exposure, such as the appearance of melanomas. In fact, due to its antioxidant capacity, fucoxanthin has been tested in several anti-aging and anti-sun cosmetic formulations [ 101 , 102 ].…”
Section: Developed Products Containing Fucoxanthin and Their Healtmentioning
confidence: 99%